Potential of Microalgae Scenedesmus obliquus Grown in Brewery Wastewater for Biodiesel Production - Teresa M. Mata (2013)
This work aims to analyze the possibility of growing microalgae Scenedesmus obliquus (S. obliquus) in a brewery wastewater as a potential candidate for biodiesel production. For this purpose S. obliquus was cultivated in a synthetic brewery wastewater at 12,000 Lux of light intensity, with a 12 h period of daily light and aeration. Under these conditions, results revealed an average lipid content of 27 % of dry-weight (dwt) biomass and average biomass and lipid concentrations of respectively, 0.90 and 0.24 g/L (of dwt biomass). The fatty acid methyl esters (FAME) transesterified from the lipids are mainly composed of saturated esters (56.4 %) among which, palmitate (C16:0) is the most significant with a relative percentage of 47.8 % (wt). With regard to the unsaturated esters, the percentage of 10.6 % (wt) obtained for linolenate (C18:3) is below the maximum limit imposed by the EN 14214: 2003 standard for this ester in biodiesel. The average molecular mass of these lipids and FAME are respectively 845.2 and 283.1 g/mol.